Inclusion of Some Raw Legume Grains as Broiler Chicks Concentrates - Dousa , B.M.; Ati, Khadiga A. Abdel; Elawad, S.M. (International Journal of Poultry Science, 2011)
A total of 200 broiler chicks were used to evaluate the effect of feeding plant concentrate substitute the imported concentrate on the performance and blood composition of broilers. Four dietary treatments containing 0%, 5%, 10% and 15% plant concentrate were formulated to meet the nutrients requirements as outlined by NRC (1994). The experiment was in a Completely Randomize Design (CRD) comprised broiler chick fed iso caloric and iso nitrogenous diet. Each treatment was replicated five times with 10 birds/replicate. The study lasted for six weeks. Parameters measured was feed intake, body weight gain, Feed Conversion Ratio (FCR), pre-slaughter weight, dressing percentage, protein efficiency, some blood parameters (glucose, cholesterol, triglyceride, total lipid, total protein, calcium and phosphorus) and profitability. Result revealed that increasing dietary level of plant concentrate had significantly (p<0.05) decreased feed intake. Whereas, birds fed diet containing 5% plant concentrate significantly (p<0.05) observed best performance. There was no significant (p>0.05) difference in blood serum glucose, total protein, calcium and phosphorus. However, birds fed on diets containing 5%, 10% and 15% plant concentrate significantly (p<0.05) recorded lower serum cholesterol than control group.